2018
DOI: 10.1042/bsr20180273
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation for polymorphisms in let-7 family in cancer risk and prognosis: a system review and meta-analysis

Abstract: miRNA polymorphisms had potential to be biomarkers for cancer susceptibility and prognosis. The mature miRNA-let-7 family was considered as the most important miRNA for the cancer incidence and progression. Recently, the promising let-7 miRNAs were reported to be associated with various cancers, but the results were inconsistent. We performed a first-reported systematic review with a meta-analysis for the association of let-7 family single nucleotide polymorphisms (SNPs) with cancer risk/prognosis. Ten studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Members of the Let-7 miRNA family have been reported to be differentially expressed in various types of cancers [25], and serum miRNA Let-7a was found to be overexpressed in LSCC subjects in the present study. In contrast, Song et al [26] demonstrated significant down-regulation of Let-7a in laryngeal cancer tissue compared to adjacent normal tissue, including 59 paired laryngeal tissues, and that Let-7a expression negatively correlated with higher TNM stage and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 61%
“…Members of the Let-7 miRNA family have been reported to be differentially expressed in various types of cancers [25], and serum miRNA Let-7a was found to be overexpressed in LSCC subjects in the present study. In contrast, Song et al [26] demonstrated significant down-regulation of Let-7a in laryngeal cancer tissue compared to adjacent normal tissue, including 59 paired laryngeal tissues, and that Let-7a expression negatively correlated with higher TNM stage and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 61%
“…In the similar lines, study by Zheng et al (2015) [ 53 ] suggested that CCND1 polymorphism may not be associated with the risk of prostate cancer. Similarly, Wang et al (2018) [ 54 ] also found no significant association between the let-7i rs10877887 and let-7a-1/let-7f-1/let-7d rs13293512 polymorphisms and overall cancer risk. In disagreement with our findings a meta-analysis by Pabalan et al (2008) [ 51 ], showed an increased cancer risk associated with CCND1 -A870G polymorphism in the human population.…”
Section: Discussionmentioning
confidence: 98%
“…We concluded that many of the existing statistically significant meta‐analyses on associations of cancer with miRNA polymorphism may not be significant under strict criteria using FPRP. There have been multiple studies assessing the noteworthiness of results from meta‐analyses identifying SNP by using FPRP; however, they only assessed a single cancer type . In spite of the limitations, our study is a systematic review to provide evidence for miRNA variance to be related to various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple studies assessing the noteworthiness of results from meta-analyses identifying SNP by using FPRP; however, they only assessed a single cancer type. 43,44 In spite of the limitations, our study is a systematic review to provide evidence for miRNA variance to be related to various types of cancer. It encourages the site-specific investigation of miRNA variant function and its associations with ethnicity.…”
Section: Discussionmentioning
confidence: 99%